A Study of Association of Trauma and Alcohol Consumption in Outpatient - Punia , R K (Journal of Indian Academy of Forensic Medicine, 2014)
Alcoholic beverages have been used in human societies since the beginning of recorded history. Alcohol related problems emerging as a major public-health concern in India. The study was conducted with the aim to highlight association of Trauma and Alcohol Consumption in Outpatient in Department of Forensic Medicine, SMS Medical College, Jaipur. A male predominance (100%) was observed with majority of the victims were of the most productive and active phases of life ranging from 21-50 years (84%). In the study, 27 cases were under influence and remaining 73 cases were not under influence but all the 100 cases had consumed alcohol or congener. Out of 100 cases, about 50% had associated injuries with alcohol consumption. The relation of alcohol consumption and health outcomes are complex and multidimensional, therefore, it is appropriate to implement policies with targeted harm reduction strategies. The crucial need, from a public health perspective, is for regular means of coordination whereby prevention of alcohol-related problems is taken fully into account in policy decisions about alcohol control and regulation in the market for alcoholic beverages.